2012
DOI: 10.1037/a0029583
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between cognitive errors and interpersonal patterns in depressed women.

Abstract: Individuals with depression process information in an overly negative or biased way (e.g., Henriques & Leitenberg, 2002) and demonstrate significant interpersonal dysfunction (e.g., Zlotnick, Kohn, Keitner, & Della Grotta, 2000). This study examined the relationship between cognitive errors (CEs) and interpersonal interactions in early psychotherapy sessions of 25 female patients with major depression. Transcripts were rated for CEs using the Cognitive Error Rating Scale (Drapeau, Perry, & Dunkley, 2008). Inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 47 publications
5
27
0
Order By: Relevance
“…These requests for attention often become bothersome and result in social partners withdrawing and becoming more hostile. In turn, rather than becoming more dependent, the depressed individual might react by becoming overly defiant and aggressive when coping with social stressors [20]. The sense of stigma and shame associated with the awareness that the skin changes are visible to the surrounding, sense of isolation, the fear of being rejected by the "healthy" environment and low self-esteem may lead to the divulgence of disturbances in the mental sphere in the form of depression, anxiety or addiction [21].…”
Section: Resultsmentioning
confidence: 99%
“…These requests for attention often become bothersome and result in social partners withdrawing and becoming more hostile. In turn, rather than becoming more dependent, the depressed individual might react by becoming overly defiant and aggressive when coping with social stressors [20]. The sense of stigma and shame associated with the awareness that the skin changes are visible to the surrounding, sense of isolation, the fear of being rejected by the "healthy" environment and low self-esteem may lead to the divulgence of disturbances in the mental sphere in the form of depression, anxiety or addiction [21].…”
Section: Resultsmentioning
confidence: 99%
“…Comfortable and trustful home environment assist in the recovery process of mentally ill patient. Schwartzman in their studies found that positive family support increased active coping by providing a context for obtaining constructive feedbacks [15]. Patients who interacted with their family members in an affirming and nurturing manner are more likely to use problem solving behaviors instead of emotion focused coping behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Schwartzman et al. () suggest that for an individual with depression, the interpersonal behaviour of ‘freeing and forgetting’ provides a degree of interpersonal distance that is similar to interpersonal withdrawal (Joiner, ). These results are also consistent with past studies that found the CEs ‘overgeneralization’ (Carver, ) and ‘personalization’ (Sayers, Kohn, Fresco, Bellack & Sarwer, ) to be associated with interpersonal difficulties.…”
Section: Interpersonal Behaviour and Depressionmentioning
confidence: 99%
“…The Schwartzman et al. () study adds to the existing literature, as it examined cognitive and interpersonal processes using a clinical sample (individuals who met criteria for depression) and observer‐rated methods. Additionally, this study examined participants’ self‐directed affiliation and autonomy behaviours, i.e., their introjections, a construct acknowledged in the cognitive‐interpersonal literature in relation to psychological well‐being (Vittengl, Clark & Jarrett, ).…”
Section: Interpersonal Behaviour and Depressionmentioning
confidence: 99%